Translation Quality of Positive Politeness in the Translated Novel “Reflected in You” - Rohman, Tefur Nur; Mustofa, Ihyak; Alfaruqy, Doni (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2024)
Most translation studies examine translation aspects; nevertheless, this study explores translation aspects combined with pragmatics, focusing on the study of positive politeness. A novel entitled Reflected in You contains many instances of complex positive politeness strategies and their translations. This novel is written by Silvia Day, a best-selling novelist. Data in the form of utterances representing positive politeness strategies were collected and analyzed to determine their types. Additionally, the translations of these utterances were assessed by three raters to evaluate their quality in terms of accuracy and acceptability. This research analyzes the types of positive politeness strategies in Reflected in You. Furthermore, the researchers examine and classify the translation strategies by using the frameworks to assess translation quality proposed byz Albir (2002) and Nababan et al. (2012). The results show that there are 12 positive politeness sub-strategies identified. The most dominant sub-strategy is the use of group identity markers, which accounts for 17 data units (34%). In this study, 8 translation techniques were identified, with the literal translation technique being the most dominant, used 22 times (37.28%). Regarding translation quality, out of 50 data samples, 43 (86%) were deemed accurate, and 40 (80%) were considered acceptable. Overall, the translation techniques applied to the utterances representing positive politeness strategies successfully conveyed the messages from the source language (SL) to the target language (TL) with clarity.